Occupational Health in Japan: A Comparative Quality of Life Study among Wellness Oriented Professionals - A, Beresniak; JP, Auray; K, Johoji; K, Toh; J, Leverett (Archives of Clinical and Biomedical Research, 2026)
Background: Quality of Life (QoL) is a multidimensional indicator of well-being, shaped by health behaviors and social context. In Japan, where appearance and social harmony are culturally valued, this study examines QoL among Amway Business Owners (ABOs)—independent entrepreneurs authorized to sell products directly to consumers and to build networks of other business owners. ABOs are routinely exposed to wellness products and entrepreneurial practices. Methods: A cross-sectional survey was conducted with 1,524 participants divided into three groups: ABO Business Leaders (n=607), ABO Consumers (n=517), and a general population control group (n=400). Two validated QoL instruments were used to assess perceived health and quality of life: the Japanese versions of the BeautyQoL instrument specific to cosmetology and the generic SF-36 Health-Related QoL questionnaire. Results: ABO Business Leaders reported the highest levels of physical and mental wellbeing, healthier lifestyles, superior scores across all BeautyQol dimensions compared to the other groups. ABO Consumers also scored higher than the control group, suggesting a dose-response relationship between wellness engagement and QoL. The analyses of the SF36 dimensions showed ABO Business Leaders outperformed the other groups in term of Vitality, Mental Health Index and General Health Perception. Conclusion: Sustained involvement in wellness-related occupations is associated with enhanced QoL in Japan. These findings highlight the psychosocial benefits of integrating health-focused practices into professional identity and suggest potential applications in public health and workplace wellbeing strategies. These results merit further confirmation in Western cultural settings, to assess their generalizability and to better understand potential cross-cultural differences.